Binary spider monkey algorithm approach for optimal siting of the phasor measurement unit for power system state estimation - Suresh Babu Palepu; Manubolu Damodar Reddy (Institute of Advanced Engineering and Science, 2022)
The phasor measurement unit (PMU) is an essential measuring device in current power systems. The advantage seems to be that the measuring system could simultaneously give voltages and currents phasor readings from widely dispersed locations in the electric power grid for state estimation and fault detection. Simulations and field experiences recommend that PMUs can reform the manner power systems are monitored and controlled. However, it is felt that expenses will limit the number of PMUs that will be put into any power system. Here, PMU placement is done using a binary spider monkey optimization (BSMO) technique that uses BSMO by simulating spider monkeys’ foraging behavior. Spider monkeys have been classified as animals with a fission-fusion social structure. Animals that follow fission-fusion social systems divide into big and tiny groups, and vice versa, in response to food shortage or availability. The method under development produced the optimum placement of PMUs while keeping the network fully observable under various contingencies. In the study published in IEEE14, IEEE24, IEEE30, IEEE39, IEEE57, and IEEE118, the proposed technique was found to reduce the number of PMUs needed.